THE MAIN DIRECTIONS OF IMPROVING THE SOCIO-ECONOMIC DEVELOPMENT OF THE REGIONS - Nabiev O. A. (European Science Publishing, 2024)
Although the first steps to introduce participatory budgeting in Uzbekistan have shown positive results, there is still a lot of work to be done to involve citizens in the budget process. The article talks about the essence of the modern trends that increase the level of socio-economic development of the regions and the main problems related to them.
Keywords: Participatory Budgeting, Participatory Budgeting, local budget revenues, local budget expenditures, livelihoods, socio-economic development.